(untitled) (Bangladesh Heart Journal, 2018)
Intraaortic balloon pump (IABP) is the most common mechanical assist device used for the treatment of low cardiac output in patients undergoing coronary artery bypass grafting (CABG). Despite recent advancement in cardiac surgery the overall mortality in patients receiving perioperative IABP remains high. In most cases the patient has poor Left ventricular (LV) function, diastolic dysfunction, recent myocardial infarction with septal rupture, heart failure and/or cardiogenic shock receiving an IABP counterpulsation support. Unfortunately patients with preserved LV function may also require IABP support to wean from cardio pulmonary bypass due to post-surgical myocardial dysfunction. This hospital-based prospective observational study evaluated 60 patients, who underwent CABG, divided into two groups. Left ventricular ejection fraction was 56.93± 7.666 in Group A compared to 41.50± 6.735 in Group B. When compared with the corresponding preoperative ejection fraction both the group found to have improved ejection fraction among the survivors at three months. Left ventricular end diastolic diameter and end systolic diameter was also found improved in both the groups (53.15± 3.231mm vs 59.47± 4.200mm and 41.52± 2.847mm vs 44.47± 3.636mm respectively). No significant difference was observed in terms of 30days mortality and postoperative outcome. Given its survival benefit, surgeons must use IABP in a pre-planned way. Here by we recommend that the use of risk prediction score for patient undergoing coronary revascularization surgery is useful. Bangladesh Heart Journal 2017; 32(2) : 94-99